2004
DOI: 10.1210/jc.2004-0553
|View full text |Cite
|
Sign up to set email alerts
|

TheInsulin-Like Growth Factor-II ReceptorGene Is Associated with Type 1 Diabetes: Evidence of a Maternal Effect

Abstract: Susceptibility to type 1 diabetes (T1D) is a complex trait, involving several loci. One of these putative loci, insulin-dependent diabetes mellitus-8 (IDDM8) at 6q, has been found to be subject to parental effects, suggesting the involvement of an imprinted gene. IGF-II receptor (IGF2R), the best-studied imprinted gene in the IDDM8 region, encodes the IGF-2 receptor, a protein involved in many biological processes, including immune function and beta-cell regeneration. Mice express only the maternal allele. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…We hypothesize that the ACAA-insertion/deletion polymorphism at the 3 0 UTR of the IGFIIR might be involved in the pathogenesis of type 2 diabetes by its regulatory functions on fetal growth and/or b cell proliferation (26). As opposed to the association of the ACAA-insertion/deletion polymorphism at the 3 0 UTR of the IGFIIR with type 2 diabetes and insulin-resistant traits described here by us, a previous study (27) showed that an IGFIIR polymorphism located at exon 16, and not the ACAAinsertion/deletion polymorphism at the 3 0 UTR, resulted in statistically significant transmission distortion in parent -offspring trios of children with type 1 diabetes. Possibly, this polymorphism influences some of the immune functions mediated by the IGF-II receptor, which has also been identified as a potential target for human autoimmune responses (28).…”
Section: Discussionmentioning
confidence: 53%
“…We hypothesize that the ACAA-insertion/deletion polymorphism at the 3 0 UTR of the IGFIIR might be involved in the pathogenesis of type 2 diabetes by its regulatory functions on fetal growth and/or b cell proliferation (26). As opposed to the association of the ACAA-insertion/deletion polymorphism at the 3 0 UTR of the IGFIIR with type 2 diabetes and insulin-resistant traits described here by us, a previous study (27) showed that an IGFIIR polymorphism located at exon 16, and not the ACAAinsertion/deletion polymorphism at the 3 0 UTR, resulted in statistically significant transmission distortion in parent -offspring trios of children with type 1 diabetes. Possibly, this polymorphism influences some of the immune functions mediated by the IGF-II receptor, which has also been identified as a potential target for human autoimmune responses (28).…”
Section: Discussionmentioning
confidence: 53%
“…For instance, there is increased transmission of the G allele of Ex16+88G>A to children with insulin-dependent diabetes mellitus from mothers compared with those with the A allele (37). This disproportionate transmission of the maternal allele along with recent evidence for imprinting of IGF2R in humans (35,38) suggest that variants in IGF2R could be important in disease risk.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, changes in methylation at the putatively polymorphically imprinted IGF2 receptor gene locus could lead to decreased IGF-II activity and small size at birth due to increased numbers of the sink IGF-II receptor (102,103). Similarly overexpression of RASGRF1, which regulates postnatal growth and is known to be imprinted in rodents, could explain the taller stature and higher IGF-I levels in IVF children.…”
Section: Candidate Genesmentioning
confidence: 99%